Prognostic Nomogram of Prognosis-Related Genes and Clinicopathological Characteristics to Predict the 5-Year Survival Rate of Colon Cancer Patients - Huang, Chao; Zhao, Jiefeng; Zhu, Zhengming (Frontiers in Surgery, 2021)
Abstract Background: The Cancer Genome Atlas (TCGA) has established a genome-wide gene expression profile, increasing our understanding of the impact of tumor heredity on clinical outcomes. the aim of this study was to construct a nomogram using data from the TCGA of prognostic-related genes and clinicopathological characteristics to predict 5-year survival of CC. Methods: Kaplan–Meier and Cox regression analysis was used to identify genes associated with 5-year survival of CC. Cox regression was used to analyze the relationship between the clinicopathological features and prognostic genes and overall survival in patients with CC, and to find independent risk factors for the prognosis of CC patients. A nomogram for predicting 5-year survival of CC was constructed by R software. Results：A total of eight genes (KCNJ14, CILP2, ATP6V1G2, GABRD, RIMKLB, SIX2, PLEKHA8P1 and MPP2) related to 5-year survival of CC were identified. Age, stage, and PLEKHA8P1 were independent risk factors for 5-year survival in patients with CC. The accuracy, sensitivity and specificity of the nomogram model constructed by age, TNM staging, and PLEKHA8P1 in predicting 5-year survival of CC were 83.3%, 83.97%, and 85.79%, respectively. Conclusion：The nomogram can correctly predict the 5-year survival rate of patients with CC, thus determining the individualized decision-making of patients with CC.